The Growth of the Great Indonesia Party (Parindra) in West Kalimantan 1937—1942 - Mohammad Rikaz Prabowo (Universitas Airlangga, 2024)
The Great Indonesia Party (Parindra) is a major party in the era of the national movement, founded by dr. Soetomo by carrying out a fusion between Boedi Oetomo (BO) and the Indonesian National Association (PBI) in 1936. Parindra has quite extensive branches, including in West Kalimantan. This research uses historical methods through heuristic, verification, interpretation, and historiography stages. Based on the analysis results, several conclusions were obtained regarding the development of Parindra in West Kalimantan. First, Parindra was present in 1936 in Pontianak, founded by R. Koempoel, A.N. Hadjarati, Mustamir, and A. Harahap, all Parindra activists. On 22 July 1938, the Pontianak branch was inaugurated, followed by Singkawang on 1 December 1938. Second, a wing of the Parindra youth organization, namely Surya Wirawan, was also established. Throughout 1939-1941, branches were established in Mempawah, Sambas, Ngabang, Tayan, Sintang, Sukadana and Nanga Bunut. Third, Parindra outlined his struggle through cooperative and open politics in facing Dutch colonialism. Parindra's struggle in the economic sector is by opening an economic union (koperasi), while in the social sector by collecting zakat and establishing reading and writing schools. As for the political field, Parindra chose to collaborate with the Persatuan Anak Borneo (PAB) organization, and held public meetings in support of GAPI’s demand for “Indonesia with a Parliament.”